Self-Medication of Corticosteroids: A Life Threatening Case Report from Pakistan - Khurshid, Hashmi Furqan; Zikria, Saleem; Hamid, Saeed; Kumar, Verma Ashutosh (Journal of Pharmacy Practice and Community Medicine)
A 70 years-old male patient with poor socioeconomic status seeks medical treatment from a quack for a minor injury. The Quack assured him to improve his health while offering him a miracle medicine that went wrong. A registered medical practitioner made a working diagnosis of the mismanaged early stage cellulitis and patient was shifted to a specialized hospital with subsequent deterioration of his health due to septicemia leading to unconsciousness. Pertinent medical history determined patient’s self-medication habits for the last 10 years including Prednisolone and Tetracycline for upper respiratory tract disorders–identified as per medicine color and shape. A number of potent antibiotics were tried but in vain. Finally the patient was diagnosed with corticosteroid induced adrenal suppression which shifted a minor injury into life threatening condition. In ICU, physician added injection Dexamethasone which regains patient’s consciousness within 3–4 hrs. It is concluded that in a country like Pakistan where provision of prescription medicines are similar to over the counter medicines, self-medication driven disease mismanagement coupled with treatment and procedural qualms for uneducated patients, mightsteer a minor health event to a life-threatening incident.
Keywords: Self-medication; Corticosteroid; Cellulitis; Septicemia; Quackery